Clinical outcomes in metastatic uveal melanoma treated with PD‐1 and PD‐L1 antibodies. Issue 21 (17th August 2016) - Algazi, Alain P.; Tsai, Katy K.; Shoushtari, Alexander N.; Munhoz, Rodrigo R.; Eroglu, Zeynep; Piulats, Josep M.; Ott, Patrick A.; Johnson, Douglas B.; Hwang, Jimmy; Daud, Adil I.; Sosman, Jeffrey A.; Carvajal, Richard D.; et al.
Abstract : BACKGROUND: Antibodies inhibiting the programmed death receptor 1 (PD‐1) have demonstrated significant activity in the treatment of advanced cutaneous melanoma. The efficacy and safety of PD‐1 blockade in patients with uveal melanoma has not been well characterized. METHODS: Fifty‐eight patients with stage IV uveal melanoma received PD‐1 or PD‐1 ligand (PD‐L1) antibodies between 2009 and 2015 at 9 academic centers. Patients who were evaluable for response were eligible for the analysis. Imaging was performed every 12 weeks and at the investigators' discretion. Safety and clinical efficacy outcomes, including the best overall response, progression‐free survival (PFS), and overall survival (OS), were retrospectively determined. RESULTS: Of 56 eligible patients, 48 (86%) had received prior therapy, and 35 (63%) had received treatment with ipilimumab. Three patients had an objective response to ipilimumab, and 8 had stable disease as their best response. Thirty‐eight patients (68%) received pembrolizumab, 16 (29%) received nivolumab, and 2 (4%) received atezolizumab. Objective tumor responses were observed in 2 patients for an overall response rate of 3.6% (95% confidence interval [CI], 1.8%‐22.5%). Stable disease (≥6 months) was observed in 5 patients (9%). The median PFS was 2.6 months (95% CI, 2.4‐2.8 months), and the median OS was 7.6 months (95% CI, 0.7‐14.6 months). There was no association between prior treatment with ipilimumab or liver‐directed therapy and PFS or OS. Treatment was well tolerated, and only 1 patient discontinued treatment because of toxicity. CONCLUSIONS: PD‐1 and PD‐L1 antibodies rarely confer durable remissions in patients with metastatic uveal melanoma. Clinical trial enrollment should be prioritized in this population. Cancer 2016;122:3344–3353 . © 2016 American Cancer Society . Abstract : In this largest retrospective series to date of patients with metastatic uveal melanoma, the objective response rate to programmed cell death receptor 1 checkpoint inhibition is 3.6%; although durable responses are rare, responses similar to those reported in patients with cutaneous melanoma are observed. These data highlight the need for ongoing clinical trials and biomarker development for uveal melanoma.See also pages 3263‐66 and 3354‐62.